American Geriatrics Society and National Institute on Aging Bench‐to‐Bedside Conference: Sensory Impairment and Cognitive Decline in Older Adults. Issue 11 (24th September 2018) - Whitson, Heather E.; Cronin‐Golomb, Alice; Cruickshanks, Karen J.; Gilmore, Grover C.; Owsley, Cynthia; Peelle, Jonathan E.; Recanzone, Gregg; Sharma, Anu; Swenor, Bonnielin; Yaffe, Kristine; Lin, Frank R.
Abstract: This article summarizes the presentations and recommendations of the tenth annual American Geriatrics Society and National Institute on Aging Bench‐to‐Bedside research conference, "Sensory Impairment and Cognitive Decline, " on October 2–3, 2017, in Bethesda, Maryland. The risk of impairment in hearing, vision, and other senses increases with age, and almost 15% of individuals aged 70 and older have dementia. As the number of older adults increases, sensory and cognitive impairments will affect a growing proportion of the population. To limit its scope, this conference focused on sensory impairments affecting vision and hearing. Comorbid vision, hearing, and cognitive impairments in older adults are more common than would be expected by chance alone, suggesting that some common mechanisms might affect these neurological systems. This workshop explored the mechanisms and consequences of comorbid vision, hearing, and cognitive impairment in older adults; effects of sensory loss on the aging brain; and bench‐to‐bedside innovations and research opportunities. Presenters and participants identified many research gaps and questions; the top priorities fell into 3 themes: mechanisms, measurement, and interventions. The workshop delineated specific research questions that provide opportunities to improve outcomes in this growing population.J Am Geriatr Soc 66:2052–2058, 2018.